2009
DOI: 10.1002/jor.20568
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐based surgical simulation of transtrochanteric rotational osteotomy for femoral head osteonecrosis

Abstract: Transtrochanteric rotational osteotomy (TRO) is one of the joint-preserving surgical treatments for osteonecrosis of the femoral head (ONFH). It can prevent collapse of the femoral head as necrotic lesions in the weight-bearing portion can be moved sufficiently to a less weight-bearing portion by anterior rotation, posterior rotation, or varus angulation. Patient selection and preoperative planning are important to determine indications for TRO. It has been reported that successful TRO requires at least 34% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Evidence has shown that small, medially located, asymptomatic lesions may be treated with observation alone, whereas the recommended options for symptomatic precollapse stage lesions are decompression 7,86-90 , osteotomy [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] , and non-vascularized or vascularized bone-grafting 90,[109][110][111] . Once the early postcollapse stage is reached, total hip arthroplasty provides consistent results; however, satisfactory results have also been demonstrated with bone-grafting [112][113][114][115][116][117][118][119][120][121][122][123][124][125] .…”
Section: Table II Decision-making Hierarchymentioning
confidence: 99%
“…Evidence has shown that small, medially located, asymptomatic lesions may be treated with observation alone, whereas the recommended options for symptomatic precollapse stage lesions are decompression 7,86-90 , osteotomy [91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] , and non-vascularized or vascularized bone-grafting 90,[109][110][111] . Once the early postcollapse stage is reached, total hip arthroplasty provides consistent results; however, satisfactory results have also been demonstrated with bone-grafting [112][113][114][115][116][117][118][119][120][121][122][123][124][125] .…”
Section: Table II Decision-making Hierarchymentioning
confidence: 99%
“…Osteotomies were suggested for treating AVN with Ficat stage of Type 2b or 3 [ 11 , 12 ]. By releasing the retinaculum, FNRO through a surgical hip dislocation approach transposed enough viable bone to the weight-bearing zone of femoral head.…”
Section: Discussionmentioning
confidence: 99%